Role of men in contraceptive decision making and use in slum area of Sinamangal, Kathmandu district. - K.C., Laxman (2011)
SUMMARY: Contraception means to prevent pregnancy. Globally slum populations are growing at alarming rates. In Nepal also slum areas / populations are increasing day by day. With increasing urbanization, political instability, poverty, urban focused facilities slum areas / populations are growing in numbers. Role of men in contraceptive decision making means increasing the numbers of men using condoms, prevent more pregnancies, support their partners to use family planning devices. This study will help to determine the contraceptive decision made by men among slum dwellers. Almost of the slum dwellers are laborers. Due to low education and poverty many of the slum dwellers are not able to achieve their good health. Due to lack of awareness they may have no knowledge on family planning devices and there may be more chance of getting more pregnancy. This study will also help to find out the reason for not using contraception by male and female slum dwellers. Due to lack of education and low availability of the family planning devices there may be low use of condoms. There is an urgent need for equity in gender relation, responsible sexual behavior and active involvement of men in reproductive health program.